One- versus two-electron oxidation of complexed guanidino-functionalized aromatic compounds - Trumm, Christine Helga; Hübner, Olaf; Walter, Petra; Leingang, Simone; Wild, Ute; Kaifer, Elisabeth; Eberle, Benjamin; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2014)
Herein, we report a rational synthetic access to dinuclear CuII complexes with radical monocationic guanidine ligands. The starting point was the first directed synthesis of a dinuclear CuII complex of the redox-active, neutral guanidino-functionalized aromatic (GFA) compound 1,2,4,5-tetrakis(tetramethylguanidino)benzene (1) as ligand by treatment of 1 with Cu(OAc)2. The neutral complex [1Cu(OAc)22] was then oxidized with several oxidizing reagents. With I2 two-electron oxidation occurred, thus leading to green salts of the dication [1Cu(OAc)22]2+. In contrast, with AgPF6 or AgSbF6 one-electron oxidation was observed to yield red salts of the monocation [1Cu(OAc)22]+, which is a three-spin system with one unpaired electron at each copper atom and at the ligand unit. Superconducting quantum interference device (SQUID) magnetometric measurements confirm a quartet electronic ground state that arises from strong ferromagnetic copper-ligand coupling. Intense charge-transfer transitions in the visible region (576 and 536 nm) were observed in the electronic absorption spectra and assigned to strong ligand-ligand (1·+←OAc) charge-transfer (LLCT) excitations. These LLCT bands open up the possibility of photoinduced redox reactions with [1Cu(OAc)22]+ driven by restoration of the aromatic system at the GFA ligand.